2005
DOI: 10.1128/jb.187.21.7317-7324.2005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Functional Characterization of theEscherichia coliBarA-UvrY Two-Component System: Point Mutations in the HAMP Linker of the BarA Sensor Give a Dominant-Negative Phenotype

Abstract: The BarA-UvrY two-component system family is strongly associated with virulence but is poorly understood at the molecular level. During our attempts to complement a barA deletion mutant, we consistently generated various mutated BarA proteins. We reasoned that characterization of the mutants would help us to better understand the signal transduction mechanism in tripartite sensors. This was aided by the demonstrated ability to activate the UvrY regulator with acetyl phosphate independently of the BarA sensor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
27
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 47 publications
5
27
0
Order By: Relevance
“…The SCFA acetate is abundant in the intestinal tracts of mammalian hosts, where it may serve as a potent activator of BarA during enteric colonization or infection (68). Alternatively, BarA-independent phosphorylation of UvrY has been observed to occur (both in vitro and in vivo) via acetylphosphate, a high-energy intermediate in the synthesis of acetate (68,69). Though phosphorylation of UvrY and other response regulators by acetyl-phosphate has been observed in various bacterial species, the physiological relevance/significance of this observation is poorly understood (70)(71)(72).…”
Section: Regulation Of the Csr/rsm Systemmentioning
confidence: 99%
“…The SCFA acetate is abundant in the intestinal tracts of mammalian hosts, where it may serve as a potent activator of BarA during enteric colonization or infection (68). Alternatively, BarA-independent phosphorylation of UvrY has been observed to occur (both in vitro and in vivo) via acetylphosphate, a high-energy intermediate in the synthesis of acetate (68,69). Though phosphorylation of UvrY and other response regulators by acetyl-phosphate has been observed in various bacterial species, the physiological relevance/significance of this observation is poorly understood (70)(71)(72).…”
Section: Regulation Of the Csr/rsm Systemmentioning
confidence: 99%
“…We found that neither the pH nor the growth stage had a significant effect on the transcription of the two reporters. The efficiency of translation of the two genes was examined by using strain KSY009, which carries a chromosomal ⌽(uvrYЈ-lacZ) translational fusion (18), and by Western blot analysis using BarAspecific antibodies (21) and crude extracts of cells grown under the conditions described above. No differences in translation of the uvrY reporter (Fig.…”
mentioning
confidence: 99%
“…Samples were subjected to electrophoresis in a sodium dodecyl sulfate-10% polyacrylamide gel, and the resolved proteins were electrotransferred to a Hybond-ECL filter (Amersham). Immunoblot analyses were subsequently performed, using BarA polyclonal antibodies as previously described (21). exp, exponential growth phase; stat, stationary growth phase.…”
mentioning
confidence: 99%
“…Three dominant mutations were isolated in the barA gene encoding the sensor protein of the BarA-UvrY phosphorelay system of E. coli. Like the rcsC2 mutation, these mutations lie within the linker domain of BarA located just upstream of the histidine kinase domain and harbor constitutive phosphatase activity (38). Constitutive kinase activity-dominant mutations were isolated in the same region of the rcsC gene of S. enterica (20).…”
Section: Discussionmentioning
confidence: 99%